Factors influencing the intention to adopt eWallet among students of Universiti Putra Malaysia - Osman, Syuhaily; Leong, Yun Yi (Human Resource Management Academic Research Society, 2021)
This research is aimed to investigate the factors influencing student’s intention to adopt eWallet in Universiti Putra Malaysia. A total of 200 students from Universiti Putra Malaysia participated in this research where they were chosen through simple random sampling method and systematic sampling method. Data were collected through self-administered questionnaires. Categorical scale and five-point Likert scale were applied to analyze the background of respondents, as well as to measure the independent and dependent variables respectively. The findings form the Pearson Correlation analysis showed that UPM students’ intention to adopt eWallet had positive relationship with perceived usefulness (r=0.846, p=0.001), perceived ease of use (r=0.773, p=0.001), perceived security (r=0.397, p=0.001) and subjective norms (r=0.528, p=0.001). Meanwhile, based on the results of multiple linear regression analysis, the model contributed a total of 77.1% and perceived usefulness appeared as the most significant factor that contributed to the intention to adopt eWallet among UPM students. Hence, the findings of this study were useful for eWallet companies and developers in providing better understanding about factors that influence consumers’ intention to adopt eWallet in order to enhance their applications and fulfil what consumers really want.